2021
DOI: 10.1177/0003489421990156
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of a Normal Sleep Study in Healthy Children with Sleep Disordered Breathing Symptoms

Abstract: Objective: To determine the prevalence and characteristics of children with normal elective polysomnography for obstructive sleep disordered breathing (oSDB) based on the American Academy of Otolaryngology-Head and Neck Surgery (AAO-HNS) guidelines. Study Design: In this retrospective cohort study, we identified patients ages 2 to 18 who underwent diagnostic polysomnography (PSG) ordered by our otolaryngology department for SDB between 2012 and 2018. Setting: All patients were seen by otolaryngologists at an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In a study at Boston Medical Center, 45% of patients with snoring and apneic symptoms undergoing elective PSG had no evidence of OSA with the criteria of AHI < 2 despite having symptoms and exam consistent with oSDB. 8 This suggests that the clinical picture alone or a lower threshold AHI score may lead to unnecessary overtreatment of OSA. Thus, some providers and studies use a threshold AHI score <1.5 or <2 as normal instead of AHI < 1 as proposed by the AASM and AAO-HNSF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study at Boston Medical Center, 45% of patients with snoring and apneic symptoms undergoing elective PSG had no evidence of OSA with the criteria of AHI < 2 despite having symptoms and exam consistent with oSDB. 8 This suggests that the clinical picture alone or a lower threshold AHI score may lead to unnecessary overtreatment of OSA. Thus, some providers and studies use a threshold AHI score <1.5 or <2 as normal instead of AHI < 1 as proposed by the AASM and AAO-HNSF.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing a lower threshold AHI score risks overdiagnosis and overtreatment of OSA. In a study at Boston Medical Center, 45% of patients with snoring and apneic symptoms undergoing elective PSG had no evidence of OSA with the criteria of AHI < 2 despite having symptoms and exam consistent with oSDB 8 . This suggests that the clinical picture alone or a lower threshold AHI score may lead to unnecessary overtreatment of OSA.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in healthy children suspected of OSA reported that 18% of children undergo surgery without objective sleep evaluation and that of the children evaluated with PSG-studies (based on parent's concern and preference for their child to have objective sleep-evaluation before surgery) only about 55% had OSA and hence might benefit from surgery [49]. This is of concern as surgery includes some immediate risk for the child and may cause complications [19] and removing this lymphoid tissue may increase longerterm respiratory, allergic, and infectious sequelae [20].…”
Section: Discussionmentioning
confidence: 99%
“…Ethnicity is a well ascribed major risk factor for childhood obesity, 29 and impacts pediatric OSA prevalence 4,30–33 . Notwithstanding few studies have addressed the influence of Hispanic ethnicity on OSA 34 .…”
Section: Introductionmentioning
confidence: 99%